Systematic review of the association between adverse life events and the onset and relapse of postpartum psychosis - Reilly, TJ; Roberts, E; Sagnay De La Bastida, VC; McGuire, P; Dazzan, P; Cullen, AE (Frontiers Media, 2023)
Postpartum psychosis is defined as a psychotic episode occurring within 4 to 6  weeks of childbirth. While there is robust evidence that adverse life events are associated with the onset and relapse of psychosis outside the postpartum period, the extent to which these contribute to postpartum psychosis is less clear. This systematic review examined whether adverse life events are associated with an increased likelihood of developing postpartum psychosis or subsequent relapse in women diagnosed with postpartum psychosis. The following databases were searched from inception to June 2021: MEDLINE, EMBASE, PsycInfo. Study level data were extracted including setting, number of participants, type of adverse event, and differences between groups. A modified version of the Newcastle-Ottawa Quality Assessments Scale was used to assess risk of bias. In total, 1933 records were identified, of which 17 met the inclusion criteria, comprising nine case–control studies and eight cohort studies. Most studies (16/17) examined the association between adverse life events and the onset of postpartum psychosis, with only in which the outcome was relapse of psychosis. Overall, there were 63 different measures of adversity examined (most of which were examined in a single study only) and 87 associations between these measures and postpartum psychosis tested across the studies. In terms of statistically significant associations with onset/relapse of postpartum psychosis, 15 (17%) were positive (i.e., the adverse event increased the risk of onset/relapse), 4 (5%) were negative, and 68 (78%) were not statistically significant. Our review highlights the diversity of risk factors examined in this field, with few attempts at replication, hence limiting the ability to conclude that any single risk factor is robustly associated with the onset of postpartum psychosis. Further large-scale studies, that attempt to replicate earlier studies, are urgently needed to determine whether adverse life events play a role in the onset and exacerbation of postpartum psychosis.